PERAN SISTEM INFORMASI AKUNTANSI MANAJEMEN DALAM MENGOPTIMALKAN KINERJA KEUANGAN PERUSAHAAN DI ERA DIGITAL - Irman Ramdhan Fauzi, M.M; Yulia Eka Rini, M.Pd; Sarah Robiatul Adawiyah, M.Pd (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
In the rapidly evolving digital era, companies face challenges in managing financial performance efficiently and responding to rapid market changes. Management accounting information systems (MAIS) have emerged as a crucial solution to these challenges, given their ability to provide integrated and real-time financial data. This study aims to explore the role of management accounting information systems (MAIS) in optimizing corporate financial performance using a qualitative descriptive literature review method. The literature review reveals that management accounting information systems (MAIS) significantly contributes to improving decision-making processes, reducing manual errors, and enhancing financial transparency. However, the implementation of management accounting information systems (MAIS) also faces challenges, particularly regarding technology adaptation and human resources. This research is expected to offer insights for companies on how to leverage management accounting information systems (MAIS) to achieve optimal financial performance in the digital age.